Evidence summary: Turmeric (curcumin) in wound management — (Limited Resources Communities — LRCs) - Watts, Robin (Cambridge Media, 2017)
Question: What is the best available evidence regarding the use of turmeric in wound management? Background: Turmeric is a plant from which the rhizome is used to prepare a spice. In Indian and Asian cultures, turmeric spice has traditionally been used as a treatment for a wide variety of conditions including wounds. It contains high concentrations of an active chemical substance curcumin. Curcumin is reported as having, among others, anti-inflammatory, antioxidant, antimicrobial and anti-cancer properties and is used to treat a wide range of conditions. There are few published studies on the use of curcumin in human wound care, with evidence primarily provided from in-vitro and in-vivo studies.